O paciente borderline na literatura psicanalítica, de 1930 a 2016 - Santos, Guilherme Geha dos (2017)
The proposition of this work is to examine the psychoanalytic literature about the psychopathological framework "borderline", from 1930 to 2016. For that reason, we realized a research on the PsycInfo searcher, with the terms "Borderline Disorder AND Psychoanalysis", that resulted in 620 papers. From them, we found 45 that composed our investigation material. After the reading and analysis of those papers, we analyzed the relations between them. Those analyses refer, among others, about the researches with the framework selected, the historical evolution of the comprehension of the framework and the various diagnostic labels that has been created as an alternative and critic of the term borderline, as well. Furthermore, we analyzed the psychodynamic comprehensions developed by the authors, which involved defense mechanisms, such as splitting, or concepts of the psychoanalytic clinic, such as the transference psychosis. Through the papers, we saw concepts being repeated, like projective identification, that permitted correlations, and new aspects being identified, such as the importance given to countertransference, that permitted the exam of divergences between authors. We will make, at the end, conclusions about the identification of a borderline object and about the scientific research with the borderline framework and psychoanalysis. These conclusions offer a perspective of analysis of the literature, allowing future researches.